ANALISIS HUKUM DALAM GUGATAN PERBUATAN MELAWAN HUKUM TERHADAP PERJANJIAN PINJAM MEMINJAM UANG (Putusan Mahkamah Agung Nomor 1872 K/Pdt/2017) - Wiwik Sri Widiarty; Rr.Ani Wijayati; Grace Rumiris Gultom (Fakultas Hukum Universitas Kristen Indonesia, 2021)
In society there are many agreements, one of which is lending and borrowing money, which is a legal relationship because the relationship was born based on an agreement. The lending and borrowing relationship can be done with an agreement between the borrower and the lender as outlined in the form of an agreement, but in practice the contents of the agreed agreement cannot always run in accordance with the applicable provisions. In certain conditions, various things can be found which result in Acts against the Law. The issues examined in this paper are what is meant by acts against the law in the Civil Code and how judges consider the evidence of illegal acts against borrowing and lending agreements (Supreme Court Decision Number 1872 K / Pdt / 2017). The research method in this writing is literature research or normative legal research obtained by reading, quoting, copying and analyzing legal principles, legal theories, doctrines, applicable regulations and court decisions that have permanent legal force. The result of research in this paper is that the definition of an act against the law in Article 1365 of the Indonesian Civil Code is: